Comparative pharmacokinetics of spectinamide 1599 after subcutaneous and intrapulmonary aerosol administration in mice. (January 2019) - Rathi, Chetan; Lukka, Pradeep B.; Wagh, Santosh; Lee, Richard E.; Lenaerts, Anne J.; Braunstein, Miriam; Hickey, Anthony; Gonzalez-Juarrero, Mercedes; Meibohm, Bernd
Abstract: Spectinamides are a novel series of spectinomycin analogs being developed for the treatment of tuberculosis. Intrapulmonary aerosol (IPA) administration of lead spectinamide 1599 has previously been shown to be more efficacious than subcutaneous (SC) administration at comparable doses. The objective of the current study was to characterize the disposition of 1599 in plasma and lungs in mice in order to provide a potential rationale for the observed efficacy differences. 200 mg/kg of 1599 was administered to healthy BALB/c mice by SC injection or by IPA delivery. Plasma and major organs were collected at specified time points until 8 h after dosing. Drug concentrations were measured by LC-MS/MS and analyzed by noncompartmental pharmacokinetic analysis. 1599 demonstrated rapid absorption into plasma after IPA and SC administration, resulting in very similar plasma exposure for both routes. In contrast, drug exposure in the lungs was 48 times higher following IPA as compared to SC administration, which is highly desirable as the lungs are the main site of infection in pulmonary TB. The higher local exposure in the lungs is likely the basis for the increased efficacy after IPA compared to SC administration. Overall, this study supports the pulmonary route as a potential pathway for the treatment of tuberculosis with 1599.